Analisis Asuhan Keperawatan Pasien Fraktur Femur Dengan Intervensi Terapi Relaksasi Nafas Dalam Terhadap Masalah Nyeri Akut Post OP - Komang Onik Rasmini; Kadek Yudi Aryawan; Luh Linda Ayu Tania (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Fracture is one of the causes of disability, one of which is due to trauma due to an accident. Fracture is a break in the continuity of bone tissue which is generally caused by pressure. Another impact that arises from fractures is that they can experience changes in the part of the body that is injured. Feeling anxious due to pain and pain. Pain management by doing deep breathing relaxation techniques is a relaxation technique is a nursing action carried out to reduce pain. Several studies have shown that deep breathing relaxation is very effective in reducing postoperative pain. To determine the effect of Deep Breath Relaxation Therapy on Acute Post-Op Pain Problems in the Blibis Inpatient Surgery Room of Wangaya General Hospital, Denpasar City. The design used in this study is a case study, the subject of this nursing analysis is a patient with post-operative Data collection instruments using interviews. Observation and physical examination, and documentation studies. Data were analyzed through assessment, nursing diagnosis, planning, implementation, and evaluation. Based on the data obtained above, the author obtained the results from the two managed patients that the first managed patient's goal was resolved with a decrease in the pain scale to 2-3 (0-10). In the second managed patient, the goal was resolved with a scale of 3-4 (0-10) by continuing the intervention of assessing the patient's vital signs, providing a comfortable position or adjusting the patient's sleeping position, teaching non- pharmacological techniques with deep breathing relaxation therapy and collaborating with doctors by administering antibiotics. The study found that deep breathing relaxation therapy interventions had an effect on acute postoperative pain problems in the surgical inpatient blibis room of the Wangaya General Hospital, Denpasar City